Vidas cotidianas en emergencia Territorio, habitantes y prácticas - Reyes, María José; Arensburg, Svenska; Póo, Ximena (Social-ediciones, 2016)
The book "Everyday Lives in Emergency: Territory, Inhabitants and Practices" brings together the work carried out by the four researches that make up the IB-JGM Nucleus of the same Name, as a space for theoretical and methodological experimentation on the points of articulation between the profession of to investigate and the profession of creating, as ways of decoding daily lives in emergencies in three territories (La Laguna Population, La Legua Population, Migration). The book is made up of texts that seek to address the questions and positions that each of the teams worked around the concept of "Everyday Lives in Emergency" in their particular investigations. In this way, the book would be organized into two large sections: the first entitled "Territory and Inhabitants" seeks to locate the singularities of the territories and the work processes of each line of research; the second, entitled "Tactics and Resistances", seeks to work on the way in which these concepts are put into play in the processes of each investigated space and in the investigative relationship. The book also has a Prologue written by the national academic María Emilia Tijoux, a chapter written by Manuel Canales and Genoveva Echeverría and a text written by the FiSura Interpretation Center.